Efectividad de las técnicas de liberación miofascial y método Mckenzie en empleados de la clínica universitaria pontificia bolivariana que presentan lumbalgia mecánica (2016)
The following article is focused in determine the degree of effectiveness of technical physiotherapy as it release myofascial and the method Mckenzie, applied in employees, of the sector administrative and medical of the clinical University Pontifical Bolivarian, that present pain lumbar acute or chronic of origin muscle. Is important mentioning that initially those employees that participated in this process application signed the corresponding consent informed in which accepted its intention voluntary of make part of this work application; also is made a questionnaire to identify, among other things, them possible factors that lead to them employees of this clinical to acquire this type of pain; within it information collected is managed to rescue that an of them main causes of pain lumbar is it bad practice of hygiene postural that used in his work professional and them positions prolonged that them employees must keep, therefore in parallel is made with them a work of education postural to awareness them on the importance of keep a correct position of the body both in stillness as in movement and of this form prevent relapses of the pathology and possibly decrease the absenteeism labor. Of equal form, is encouraged to each one of them participating and to some of their companions of work, to the realization daily of a program of conditioning physical or gymnastics labor (pauses active) that les allow exit of its routine of work, decrease the tension to level Musculoskeletal and improve your state of mood, all this to address to them participating of a way more integral. After the application of the questionnaire and of the above mentioned techniques, was carried out a comparison between the two to determine their effectiveness and to reach a conclusion, finally a final questionnaire was administered or satisfaction whose purpose was to identify the results of the implementation of the techniques, the degree of satisfaction of the participants, regarding the same and in the same manner to determine significant was for them the realization of labor gymnastics and the implementation of guidelines of hygiene posture.